Statistical Optimization of AC/TiO2-Cu Composite via Response Surface Methodology (RSM) / Noorulayuni Atiqah Yaacob ... [et al.] - Yaacob, Noorulayuni Atiqah; Khasri, Azduwin; Mohd Salleh, Noor Hasyierah; Mohd Ridzuan, Mohd Jamir (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
AC/TiO2-Cu composite was synthesized via microwave-assisted sol gel method and acts as ternary composite photocatalyst for the removal of antibiotic from an aqueous solution under UV light irradiation through adsorption/photodegradation process. In this study, a statistical optimization experimental design was performed using a face-centered central composite design in response surface methodology for optimizing the synthesize parameters of AC/TiO2-Cu composite. The influence of experimental factors such as AC/TiO2 ratio, Cu dosage, and irradiation power with adsorption-photodegradation performance as the response were investigated.